2021
DOI: 10.1101/2021.04.22.440892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grandmaternal smoking during pregnancy is associated with differential DNA methylation in their grandchildren

Abstract: The idea that information can be transmitted to subsequent generation(s) by epigenetic means has been studied for decades but remains controversial in humans. Epidemiological studies have established that grandparental exposures are associated with health outcomes in their grandchildren, often with sex-specific effects; however the mechanism of transmission is still unclear. We conducted Epigenome Wide Association Studies (EWAS) to test whether grandmaternal smoking during pregnancy is associated with altered … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This study shows a similar association with the PGM smoking by demonstrating a reduced chance of the granddaughter having a religious belief. This accumulating evidence of smoking by a grandmother in pregnancy being associated with a sex-specific outcome is now complemented by results of DNA methylation in the maturing grandchild (age [15][16][17] that indicate different associations depending on the type of grandmother, and the sex of the grandchild [18].…”
Section: Putting the Results In Contextmentioning
confidence: 96%
See 1 more Smart Citation
“…This study shows a similar association with the PGM smoking by demonstrating a reduced chance of the granddaughter having a religious belief. This accumulating evidence of smoking by a grandmother in pregnancy being associated with a sex-specific outcome is now complemented by results of DNA methylation in the maturing grandchild (age [15][16][17] that indicate different associations depending on the type of grandmother, and the sex of the grandchild [18].…”
Section: Putting the Results In Contextmentioning
confidence: 96%
“…We have shown that the changes associated with potential epigenetic environmental exposures such as grandmother smoking in pregnancy are associated with changes in DNA methylation levels at specific CpG sites, including on the X chromosome of the grandchild [18]. There is also abundant evidence from experimental studies that traumatic events can have effects on the DNA methylome for several generations [e.g.…”
Section: Biomarkers Supporting the Epigenetic Consequences Of Smoking And Traumatic Exposuresmentioning
confidence: 99%
“…This raises the possibility that an epigenetic effect involving the X chromosome may be involved. Intriguingly, it has recently been shown that the smoking of the paternal grandmother is, as predicted, associated with differences in DNA methylation at CpG sites on the X chromosome of the granddaughter but not the grandson [ 7 ].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, there is evidence of sex-specific transgenerational associations in grandchildren when the paternal grandmother has smoked in pregnancy. In parallel-specific DNA, methylation changes have been shown in granddaughters (but not grandsons), whose paternal grandmothers smoked in pregnancy [ 7 ]; in early-onset myopia, these changes were particularly linked to genes known to be associated with myopia, thus indicating possible biological plausibility for the myopia association [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar intergenerational findings are often thought to be due to epigenetic effects, with DNA methylation being the mechanism most often quoted. Elsewhere, using blood samples from these F3 grandchildren, Watkins et al (2022) have identified different methylation markers associated with smoking in pregnancy of the F1 maternal as well as the F1 paternal grandmothers. However, it is premature to speculate further on possible mechanisms for our findings until confirmatory evidence is available from other cohorts.…”
Section: Discussionmentioning
confidence: 99%